Results of a combination of bleomycin and triamcinolone acetonide in the treatment of keloids and hypertrophic scars Resultados de uma combinação de bleomicina e triamcinolone acetonide no tratamento de quelóides e cicatrizes hipertróficas - Francisco Miguel Camacho-Martínez; Elena Rodríguez Rey; Francisco Camacho Serrano; Adriana Wagner (Sociedade Brasileira de Dermatologia, 2013)
While treatment of keloids and hypertrophic scars normally shows modest results, we found that treatment with bleomycin was more promising. The present study was divided into two parts. In the first part the aim was to show the results using a combination of bleomycin and triamcinolone acetonide per cm2 (BTA). In the second part the objective was to determine the response to both drugs in large keloids that were divided into 1 cm2 squares, treating each square with the dose previously used. In the first part of the study, the clinical response of 37 keloids ranging from 0.3 to 1.8 cm2 treated with BTA were followed up over a period of 1- 2 years. 0.375 IU bleomycin and 4 mg triamcinolone acetonide were injected every 3 months. In the second part of the study we reviewed the clinical response in six patients with large keloids. The monthly dose administered never exceeded 3 IU of bleomycin. The first study showed 36 keloids (97.29%) softening after the first dose. In the second study, 5 showed different responses (the response was complete in the four smaller keloids). The largest keloid needed 9 doses to achieve an improvement of 70%. In conclusion, combined treatment with 0.375 IU of bleomycin and 4mg of triamcinolone acetonide to 1 cm2 was considered to be an acceptable procedure for the treatment of keloids. The best results were obtained in keloids over 1 cm2 or when divided into 1 cm2 square areas. Larger series need to be performed in order to confirm these results.. Enquanto normalmente o tratamento de queloides e cicatrizes hipertróficas mostra resultados moderados, o tratamento com bleomicina revelou resultados mais promissores. Este estudo foi dividido em duas partes. Na primeira parte, o objetivo foi mostrar os resultados da utilização de uma combinação de bleomicina e acetonido de triancinolona por cm2 (BAT). Na segunda parte, o objetivo foi determinar a resposta aos dois medicamentos em queloides grandes, que foram divididos em quadrados de 1 cm2, tratando cada quadrado com a dose utilizada anteriormente. Na primeira parte do estudo, a resposta clínica de 37 queloides de 0,3 to 1,8 cm2 tratados com BAT foi monitorada por um período de 1 a 2 anos. Injeções de 0,375 UI de bleomicina e 4 mg de acetonido de triancinolona foram aplicadas a cada 3 meses. Na segunda parte do estudo, revisamos a resposta clínica em 6 pacientes com queloides grandes. A dose mensal administrada nunca excedeu 3 UI de bleomicina. O primeiro estudo mostrou que 36 queloides (97,29%) amoleceram após a primeira dose. No segundo estudo, 5 mostraram diferentes respostas (a resposta foi completa nos quatro queloides menores). O queloide maior necessitou de 9 doses para apresentar melhora de 70%. Concluindo, o tratamento combinado com 0,375 UI de bleomicina e 4 mg de acetonido de triancinolona por cm2foi considerado um procedimento aceitável para o tratamento de queloides. Os melhores resultados foram obtidos em queloides com mais de 1 cm2 ou divididos em áreas de 1cm2. Estudos mais amplos deveriam ser realizados, para confirmar esses resultados.